The Contribution of Servant Leadership, Change Management, Religiosity and Work Motivation Towards Teacher Performance - Ni Made Suparmiti; I Made Yudana; I Wayan Widiana (Universitas Pendidikan Ganesha, 2026)
Teacher performance is not yet optimal and is influenced by factors such as servant leadership, the principal’s change management, religiosity, and teachers’ work motivation. This study aims to analyze the contribution of these four variables to the achievement of teacher performance. This research is a quantitative study with an ex post facto design. The population consisted of all 58 teachers of SMP Negeri 1 Abiansemal, all of whom were selected as the research sample. Data were collected using a survey method. The data collection instrument was a closed-ended questionnaire using a Likert scale that had been tested for validity and reliability. The data were analyzed using regression analysis and partial correlation to determine the contribution of each variable to teacher performance. The results indicate that servant leadership, change management, religiosity, and work motivation, both partially and simultaneously, have a positive and significant contribution to teacher performance, with a simultaneous contribution of 79.3%. Religiosity and work motivation were the most dominant variables contributing to the improvement of teacher performance. This study concludes that improving teacher performance can be achieved through strengthening service-oriented principal leadership, effective change management, and the development of teachers’ religiosity and work motivation. The implications of this study emphasize the importance of school policies in building a values-based work culture, providing continuous professional development, and establishing support systems that enhance teachers’ intrinsic motivation to support the improvement of educational quality.